Fresno County Bar Association Luncheon with Boalt Hall Dean Jesse Choper at Smuggler's Inn - Watkins, Howard::::::::: (1989)
Dean Jesse Choper, Leo Koligian, Fresno County Bar Association President Dana French and Fresno County Bar Association Vice-President Thomas Tusan